2018
DOI: 10.1111/1471-0528.15150
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum venous thromboembolism prophylaxis may cause more harm than benefit: a critical analysis of international guidelines through an evidence‐based lens

Abstract: Based on prediction models and expert opinion, most obstetric venous thromboembolism guidelines recommend low‐molecular‐weight heparin for many postpartum women, including most delivering by caesarean. Scrutiny reveals major oversights: prediction models are based on studies that report asymptomatic deep vein thrombosis; risk estimates are not adjusted for time exposure; and harm caused by heparin has been overlooked. The benefits of heparin are exaggerated and its harms are under‐appreciated. Estimates of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 73 publications
(145 reference statements)
0
66
0
1
Order By: Relevance
“…Although arguably the best‐quality data exist to address PA‐VTE risk reduction in women with a personal VTE history or inherited thrombophilia, these 2 categories of risk factor are rare (<1% in a recent large prospective study and intense debate . In particular, the balance of thrombosis and bleeding risk is uncertain, and it is noteworthy that the 2018 ASH guideline panel highlighted important research needs, including a requirement for more data on the absolute VTE risk in women with combinations of known risk factors .…”
Section: Reducing the Risk Of Vte In Pregnancymentioning
confidence: 99%
“…Although arguably the best‐quality data exist to address PA‐VTE risk reduction in women with a personal VTE history or inherited thrombophilia, these 2 categories of risk factor are rare (<1% in a recent large prospective study and intense debate . In particular, the balance of thrombosis and bleeding risk is uncertain, and it is noteworthy that the 2018 ASH guideline panel highlighted important research needs, including a requirement for more data on the absolute VTE risk in women with combinations of known risk factors .…”
Section: Reducing the Risk Of Vte In Pregnancymentioning
confidence: 99%
“…A review by Kotaska discusses how the incidence of venous thromboembolism (VTE) has been overestimated and shows how it can be corrected and adjusted. Using evidence based analysis, this review demonstrated that assuming 70% protection with LMWH in a young woman approximately 20 years of age with a body mass index of 32 kg/m 2 after a cesarean delivery, the NNT to prevent one VTE would be 4300 similar women based on a VTE risk of 1.1/1000 in the first 6 weeks postpartum.…”
Section: Venous Thromboprophylaxis In Postpartum Womenmentioning
confidence: 99%
“…This review importantly also discussed harm from LMWH in postpartum patients. It highlighted the risk of significant hemorrhage and wound hematoma to be 0.3%–1.1% and 2.1%, respectively, and that the NNT to prevent one pulmonary embolism death is 360 000 …”
Section: Venous Thromboprophylaxis In Postpartum Womenmentioning
confidence: 99%
“…Lindqvist's algorithm‐based 5% incidence of symptomatic VTE over 9 months would equate to an incidence of 6600 per 100 000 person‐years, implausibly 10 times greater than the incidence of VTE observed by Sultan and colleagues after caesarean delivery (CD) . For the postpartum period alone, Lindqvist's projected risk would be 1.5%, which is three times greater than the 0.5% incidence of asymptomatic deep vein thombosis (3/560) observed in five studies that screened women after CD …”
mentioning
confidence: 90%
“…Lindqvist and Biasoletto for continued debate . The incidences of venous thromboembolism (VTE) cited in my paper are not taken from Scandinavian case‐control studies, rather from prospectively collected data on 380 000 reproductive‐age women in the U.K. at a time when LMWH was not commonly used …”
mentioning
confidence: 99%